Development of Flipbook-Based Interactive Media in Science and Science Subjects, Story Materials about My Region - Erdiyavita, Naili Zakiyah; Rusmawati, Retno Danu; Rohman, Ujang (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2025)
This research aims to develop FlipBook-based Interactive Media in the Science and Technology subject of News about My Region. To produce a valid instrument, the instrument that will be given to students will be tested for the validity and reliability of the instrument. This test will be carried out on students as test subjects on students. This research has succeeded in developing flipbook-based interactive media that is designed to support a more effective and interesting learning process. Based on the results of the feasibility test involving material and media experts, as well as trials on users (students), this media is considered suitable for use in learning. The results of the study show that flipbook-based interactive media can increase students’ interest and involvement in the learning process, make it easier to understand the concepts taught, and increase interactivity between students and the material presented. This media also provides convenience in terms of managing learning materials that are more dynamic and flexible, so that they can be adjusted to the needs of students. The results of the evaluation in terms of practicality and effectiveness show that the use of this media can improve the quality of learning, because students are more active in participating in learning activities.